Mecanismos de lucha contra la corrupción: Programas de cumplimiento en la contratación directa. - Portilla Archi, Gerson Kevin (2023)
The present investigation focuses on the institution called Compliance or Regulatory Compliance Programs in the framework of direct contracting in order to make it as one more element in the fight against corruption. The idea is followed that the best way to deal with corruption is prevention, that is, to demand or promote that private companies apply a culture of prevention in the face of possible breaches of legal norms. Direct hiring follows a kind of subjective attributions so that the representative of the public entity can contract directly with a private company to satisfy an emergency or urgent need, so it would be convenient to promote a culture of prevention or application of Compliance to companies. private companies that want to be contracted directly with a public entity.